Loxodontomys micropus (Rodentia: Cricetidae) - Teta, Pablo Vicente (2009)
Loxodontomys micropus (Waterhouse, 1837) is a cricetid commonly called the southern pericote. A moderately large, heavy-bodied rodent, it is 1 of the 2 species in the genus Loxodontomys. This cricetid occurs in southern Chile and southwestern Argentina. It prefers humid, dense grasslands, meadows, shrubby steppes, and mixed or open-canopied Nothofagus forests. L. micropus is categorized as of least concern.